Estimativas das componentes da radiação solar incidente em superfícies inclinadas baseadas na radiação global horizontal - Souza, Adilson P.; Escobedo, João Francisco [UNESP]; Dal Pai, Alexandre [UNESP]; Gomes, Eduardo N. [UNESP] (Universidade Federal da Paraíba (UFPB) Ccsa, 2011)
Statistics equations and validations with groups of annual and monthly data were evaluated for global, direct and diffuse solar radiation components incident on the tilted surface to 12.85, 22.85 and 32.85 degrees with the face North, in climate and geographical conditions of Botucatu, SP. It was employed the fractions of three components of extraterrestrial radiation in correlation with the coefficient clearness index horizontal plane, in a database of April/1998 to December/2007, whose measures at different periods in three inclinations, however concomitant to the horizontal plane. Increasing the angle of the surface led to increased scattering of the daily values of clearness index for inclined and horizontal surfaces. In annual groups, the lower performances were observed in the estimation of inclined daily diffuse radiation, with maximum Root Mean Square Error to 3.89 MJ m(-2) d(-1) (43.65%) and adjustments around 62%. In estimates of global and direct components of solar radiation on inclined planes, both annual and monthly equations can be applied, with performance dependents to climatic conditions.
Estimates of solar radiation components on a tilted surface based on global horizontal radiation
Keywords: clearness index; indicate estatistical; modeling